Comparing the immediate effect of pneumatic and conventional knee braces on gait, satisfaction and pain in patients with knee medial osteoarthritis. (2nd November 2022) - Saeedi, Hassan; Rezaee, Mehdi; Daryabor, Aliyeh; Khosrav, Mobina; Pour, Samira Hassan
Abstract : Background/aims: Knee braces can change loading direction on knees in people with osteoarthritis, thereby reducing symptoms and progression of the disease. The aims of this study were to explore the immediate effect of two types of braces, a pneumatic knee brace with air pressure embedded in a sandal cuff (sandal cuff pressure) and a conventional knee brace on gait, pain and satisfaction during walking in patients with knee medial osteoarthritis. Methods: A total of 28 patients with knee medial osteoarthritis were assigned to two groups, 14 patients used a conventional brace and 14 used a prototype brace with a pneumatic system, which was designed and fabricated by the authors, and followed the mechanism of variable pressures in the stance and swing phases of a gait cycle in a patient's knee. The gait parameters (walking self-selected speed, cadence, step length, knee range of motion, and maximum knee adduction moment, walking speed, cadence and step length) were measured with a Kistler force plate and Vicon motion analysis under two conditions: with and without brace for the conventional brace group, and under three conditions of no brace, brace with sandal cuff pressure, and brace without sandal cuff pressure for the pneumatic brace group. Patients' pain and satisfaction were also measured using a visual analogue scale and Likert scale respectively. Results: Both groups showed a significant reduction in maximum knee adduction moment and pain wearing braces in comparison to no brace during walking ( P <0.05). The knee range of motion was significantly decreased in the pneumatic brace group with and without sandal cuff pressure compared with no brace ( P <0.001). No significant difference was found for any of the variables when using the pneumatic brace with and without sandal cuff pressure ( P >0.05). In the between-group comparison, only patients' satisfaction was significantly reduced when using the pneumatic brace in both walking with ( P =0.041) and without ( P =0.02) sandal cuff pressure compared to those using the conventional brace. Conclusions: Both conventional and pneumatic braces led to reduced knee adduction moment and pain in patients with knee osteoarthritis. However, using a pneumatic brace reduced the knee range of motion and satisfaction of patients, which could be because the brace was a prototype.